2013
DOI: 10.1152/ajpheart.00159.2013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF-κB activation by a novel IKK inhibitor reduces the severity of experimental autoimmune myocarditis via suppression of T-cell activation

Abstract: NF-κB, which is activated by the inhibitor of NF-κB kinase (IKK), is involved in the progression of inflammatory disease. However, the effect of IKK inhibition on the progression of myocarditis is unknown. We examined the effect of IKK inhibition on the progression of myocarditis. Lewis rats were immunized with porcine cardiac myosin to induce experimental autoimmune myocarditis (EAM). We administered the IKK inhibitor (IMD-0354; 15 mg·kg(-1)·day(-1)) or vehicle to EAM rats daily. Hearts were harvested 21 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 49 publications
(116 reference statements)
2
10
0
Order By: Relevance
“…In our cells, this increased IκBα phosphorylation did not appear to be due to a higher IKK-αβ-complex kinase activity after TLR activation, as observed in T cells [29]. Other processes, such as nondegradative polyubiquitination, have been reported to be crucial for IκB kinase (IKK) activation [30].…”
Section: Discussionsupporting
confidence: 64%
“…In our cells, this increased IκBα phosphorylation did not appear to be due to a higher IKK-αβ-complex kinase activity after TLR activation, as observed in T cells [29]. Other processes, such as nondegradative polyubiquitination, have been reported to be crucial for IκB kinase (IKK) activation [30].…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, we screened multiple related compounds and found that N-(3,5-bis-trifluoromethyl-phenyl)-5-chloro-2-hydroxybenzamide (IMD 0354) is a non-ATP binding competitive and selective molecular inhibitor of IKK-β. IMD 0354 has been reported in several studies as an effective agent for the treatment of acute and subacute inflammatory diseases including myocarditis, pulmonary arterial hypertension, and diabetic retinopathy via the suppression of NF-κB activation in various cells, such as pulmonary arterial smooth muscle cells or myocardial cells [18][19][20][21] . There are considerable issues in regard to the drugs for osteoporosis treatment currently.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the evidence which suggests that myocarditis and inflammatory cardiomyopathy are autoimmune diseases come from animal models [1, 2]. The macrophages and T lymphocytes were found to be directly engaged in cell-mediated immune mechanism in experimental autoimmune myocarditis (EAM) [35].…”
Section: Introductionmentioning
confidence: 99%